Perspectivas do envelhecimento ativo e saudável na visão da equipe pedagógica do ensino básico - Silva, Maria Laura Montanher Pereira da (Universidade Federal de São Carlos, 2025)
Population aging is an increasing reality and requires reflection across various sectors of society, including education. The school, as a space of development, plays a fundamental role in building a culture that values all stages of life and combats ageism. This work aligns with the guidelines of the Decade of Healthy Ageing plan (2021–2030), proposed by the World Health Organization, which encourages intersectoral actions to promote healthy aging, inclusion, and respect for older people, beyond reflecting on how aging is perceived within the school environment by some education professionals. Objective: Identify how members of pedagogical teams in municipal basic education perceive their own aging. This study also aims to review the literature on aging and education, especially in the context of pedagogical teams and the school environment. Methodology: This study adopts both qualitative and quantitative approaches, focusing on exploratory and descriptive aspects. Primary data were obtained from the database of the research group "Law, City, and Aging" and analyzed using descriptive statistics and content analysis, based on the components of healthy and active aging. Results: In the literature review (Stage 1), studies published between 2013 and 2023 were surveyed, and 445 publications in the SciELO and CAPES Portal databases were found, using three to four descriptors with the intersection of the boolean operator “and”. After analyzing titles and abstracts, 442 were excluded: 20 for being duplicates and 422 for incompatibility with the theme, resulting in 3 relevant Brazilian studies focused on planning, inclusion, and the role of pedagogical coordination. To strengthen the theoretical framework, an additional search was conducted for 2024 publications using the same criteria. In Stage 2, focused on collecting responses from the research group's database, 19 participants responded to the pre-questionnaire and 7 to the post-questionnaire, the majority being women aged between 40 and 49 years, with postgraduate education. The analysis indicated that the intrinsic capacity component was the most significant in how participants think about, act on, and envision their aging process, with answers highlighting concepts such as independence, autonomy, and mental clarity, among others. Conclusion: Both before and after the workshop, the pedagogical team’s perception was centered on preserving physical and cognitive conditions, associated with autonomy, mental clarity, and functionality. Although, after the intervention, elements valuing subjective and psychosocial aspects, such as interpersonal relationships and knowledge sharing emerged, the environmental component was scarcely mentioned. Reflecting on aging within the school context is essential to deconstruct stigmas, strengthen intergenerational education, and promote pedagogical practices aligned with the guidelines of the Decade of Healthy Ageing, which demands investment in ongoing training and institutional commitment.
Prospects for active ageing from the point of view of the elementary school pedagogical team
Keywords: Envelhecimento; Pessoa idosa; Educação básica; Professores; Planejamento; Aging; Older person; Basic education; Teachers; Planning; OUTROS; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO